Entropy numbers and the widths of the classes $B_{p,θ}^r$ of periodic functionsof many variables - Romanyuk, A. S. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We establish the exact order estimates for the entropy numbers of the Nikol’skii – Besov classes of periodic functions of two variables in the space $L_∞$ and use the obtained results in estimating the lower bounds for Kolmogorov, linear, and trigonometric widths. We also study the behavior of similar approximating characteristics of the classes $B_{p,θ}^r$ of periodic functions of many variables in the spaces $L_1$ and $B_{1,1}$.